Application of demand-driven km at pt. Jawasoft - Rusmana Adi, Rajendra; Hidayat Tjakraatmadja, Jann (The Indonesian Journal of Business Administration, 2016)
Abstract— Software development is an industry in which the output of workers depends to a large extent from their knowledge. With no experience in knowledge management programs, PT Jawasoft has suffered problems with unbalanced developer performance, loss of knowledge due to staff turnover, and inconsistent application of best practices. To ensure maximum effectiveness of the KM program while being resource efficient, Talisayon’s (2014) Demand-driven KM framework is chosen amongst other KM frameworks such as Jarrar (2002) and Wiig (1999). In this framework, it is essential to find out what the knowledge needs of the organization is because it will determine what initiatives to execute. This question was answered using qualitative methods: one-on-one interviews with each software developer, coding of the transcript in accordance with a conceptual framework of the software development process, building a conceptually clustered matrix of the responses, and finally ordering the issue types by most frequently mentioned. From the analysis 13 issues were identified with the top 3 issues being incomplete requirements at the start of the task, requirements not communicated clearly to the developer, and unfamiliarity with the business logic of the application. These 3 issues were analyzed using a people, process, and technology approach and also Talisayon’s generic types of needed knowledge. As the result of the analysis 4 main initiatives are suggested: recruitment of a dedicated business analyst, holding regular feature meetings with clients, holding an after-action review after each problematic task, and regular addition of knowledge asset into a central repository. Keywords: Knowledge management, demand-driven KM, software development